VIRTUAL SCREENING OF POMEGRANATE (Punica granatum) CHEMICAL CONSTITUENTS FOR KINASE DOMAIN OF HUMAN HER2 AS A DRUG TARGET FOR COLON CANCER - JAYNTHY CHELLAM (International Journal of Pharma and Bio Sciences, 2015)
The entire world is now looking for natural and medicinal plants as a supplement for chemical drugs. The popularity of herbal medicine is very common in developing countries, many scientists and researchers are concentrating more on herbal plants and fruits. We all know that cancer is one of the most dreadful diseases. One among the cancer is Colorectal cancer (CRC), the fourth most common cancer in men and the third in women worldwide. The Kinase domain of Human HER2 is one of the important therapeutic drug targets for colon cancer and it belongs to ErbB family In this current study, we have carried out computational biology work in virtual screening on pomegranate chemical constitutes for colon cancer. Results show that compounds such as Pelletierine, Mannite and N-methylisopelletierine are almost docked in all protein cavities with different dock scores in each site. Arg residues present in the drug target protein play an important role in receptor ligand interaction with compounds. But clinical trials and experimental results are needed to be carried out for each individual compounds to prove its bioefficay.